Gamified Language Learning Applications: Enhancing Motivation and Speaking Skills of First-Semester Informatics Engineering Students at Politeknik Negeri Bengkalis - Desi Wahana; pretti Ristra (Juliet, 2026)
This study investigates the impact of gamified language learning applications on the motivation and speaking skills of first-semester Informatics Engineering students at Politeknik Negeri Bengkalis. Using a quasi-experimental design with 60 participants, the study compared an experimental group using gamified apps like ELSA Speak and Duolingo against a control group following conventional methods. Quantitative data from pretests and posttests were analyzed using independent-sample t-tests, while qualitative insights were gathered through structured questionnaires. The results revealed a transformative effect: the experimental group achieved significantly higher t-test scores in motivation (t=8.76, p<0.001) and speaking proficiency (t=9.12, p<0.001) compared to the control group. These findings were reinforced by a "Very High" perception score of 4.58 in the experimental group, contrasted with the control group’s moderate score of 3.16. Gamification elements such as leaderboards and immediate feedback effectively satisfied students' psychological needs for competence and autonomy, while providing a "safe space" that reduced speaking anxiety. The study concludes that gamified tools are a superior pedagogical tool for technical students, offering a strong empirical basis for integrating digital pedagogies into the English for Specific Purposes (ESP) curriculum to foster more engaging and effective learning experiences.